(untitled) (Marketing Journal, 2026)
Abstract This article examines the theoretical and methodological aspects of applying marketing approaches in the effective management of a regionʼs investment potential. The role of the territorial marketing concept in enhancing investment attractiveness is revealed, and scientific proposals and recommendations are developed to improve the mechanisms for assessing, forming, and managing investment potential. Keywords: territorial marketing, investment potential, investment attractiveness, marketing strategy, territorial branding, investment climate, investment potential, investment activity, regional economy, exogenous and endogenous factors of economic growth in the region.